HORYZONS trial: protocol for a randomised controlled trial of a moderated online social therapy to maintain treatment effects from first-episode psychosis services. Issue 2 (3rd February 2019) - Alvarez-Jimenez, Mario; Bendall, Sarah; Koval, Peter; Rice, Simon; Cagliarini, Daniela; Valentine, Lee; D'Alfonso, Simon; Miles, Christopher; Russon, Penni; Penn, David L; Phillips, Jess; Lederman, Reeva; et al.
Abstract : Introduction: Specialised early intervention services have demonstrated improved outcomes in first-episode psychosis (FEP); however, clinical gains may not be sustained after patients are transferred to regular care. Moreover, many patients with FEP remain socially isolated with poor functional outcomes. To address this, our multidisciplinary team has developed a moderated online social media therapy (HORYZONS) designed to enhance social functioning and maintain clinical gains from specialist FEP services. HORYZONS merges: (1) peer-to-peer social networking; (2) tailored therapeutic interventions; (3) expert and peer-moderation; and (4) new models of psychological therapy (strengths and mindfulness-based interventions) targeting social functioning. The aim of this trial is to determine whether following 2 years of specialised support and 18-month online social media-based intervention (HORYZONS) is superior to 18 months of regular care. Methods and analysis: This study is a single-blind randomised controlled trial. The treatment conditions include HORYZONS plus treatment as usual (TAU) or TAU alone. We recruited 170 young people with FEP, aged 16–27 years, in clinical remission and nearing discharge from Early Psychosis Prevention and Intervention Centre, Melbourne. The study includes four assessment time points, namely, baseline, 6-month, 12-month and 18-month follow-up. The study is due for completion in July 2018 and included a 40-month recruitment period and an 18-month treatment phase. The primary outcome is social functioning at 18 months. Secondary outcome measures include rate of hospital admissions, cost-effectiveness, vocational status, depression, social support, loneliness, self-esteem, self-efficacy, anxiety, psychological well-being, satisfaction with life, quality of life, positive and negative psychotic symptoms and substance use. Social functioning will be also assessed in real time through our Smartphone Ecological Momentary Assessment tool. Ethics and dissemination: Melbourne Health Human Research Ethics Committee (2013.146) provided ethics approval for this study. Findings will be made available through scientific journals and forums and to the public via social media and the Orygen website. Trial registration number: ACTRN12614000009617; Pre-results.